STUDI EMPIRIS PENGARUH JENIS LAYANAN DAN KUALITAS LAYANAN TERHADAP KEPUASAN PENGGUNA JASA EKSPEDISI SICEPAT DI PURWOKERTO: PENDEKATAN ANOVA DUA ARAH (Kohesi: Jurnal Sains dan Teknologi, 2025)
As competition intensifies in Indonesia's expedition service industry, customer satisfaction has become a crucial factor for maintaining loyalty. This study aims to analyze the influence of service type (REG, BEST, HALU), service quality (reliability, responsiveness, security), and their interaction on the satisfaction level of SiCepat expedition service users in Purwokerto. This research employs a quantitative approach using the two-way ANOVA method. Data was collected via questionnaires from 60 SiCepat users in Purwokerto, selected through simple random sampling. Data analysis was performed using SPSS after the assumptions of normality and homogeneity of variance were met. The analysis results indicate that there was no significant influence from either service type (p=0.152) or service quality (p=0.817) on user satisfaction. Furthermore, no significant interaction effect was found between these two factors (p=0.301). A negative Adjusted R-Squared value (-0.005) indicates that the tested model was ineffective in explaining the variance in customer satisfaction. This study concludes that the differences in service type and quality offered by SiCepat are not the primary determinants of user satisfaction in Purwokerto, suggesting that other factors such as price, delivery speed, or ease of tracking may be more dominant.